Kajian Pemanenan Air Hujan Skala Individual Untuk Pemenuhan Air Baku Wilayah Pesisir (Wilayah Kajian: Desa Topang, Kecamatan Rangsang, Kabupaten Kepulauan Meranti) - Prabowo, Noor Arief; Sasmita, Aryo; Reza, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Topang Village is the only village in Meranti Regency whose territory is on one island. The source of clean water used by the people of Topang Village for drinking and cooking needs is water produced from rain harvesting, but the rainwater harvesting system in Topang Village is less effective and still uses traditional methods. Supported by the Raincyle Standard v2.0 program based on the roof's drip line which forms the boundary of the catchment area as well as water needs based on the number of family members of each type of house. Rainfall parameters have an influence on quantitative harvesting of individual scale rainwater obtained from hail Rain Cycle v2.0 to meet raw water needs in Topang Village, Rangsang District, Meranti Island District can use 2 tanks can contribute water the fulfillment of raw water needs with Catchment Area of 49 m2. Keywords : Meranti Islands Regency, Topang Village, Raw Water.